THE RESULTS OF THE DEVELOPMENT OF PREVENTIVE BEHAVIORS AGAINST COVID-19 OF THE PUBLIC HEALTH VOLUNTEER IN NAKHON PHANOM PROVINCE - Wongchansri, Suttichai (Primary Health Care Journal (Northeastern Edition), 2023)
This research is quasi-experimental. The objective was to compare the mean scores on knowledge and behavior in preventing COVID-19 disease. Before and after organizing activities to develop behaviors for the prevention of COVID-19 The sample consisted of 369 village health volunteers in Nakhon Phanom province who were randomized by purposive sampling. They received activities to develop behaviors for preventing COVID-19, including demonstrations and self-training, for a period of 6 weeks. The tools used for data collection were questionnaires. The data were analyzed using the statistical distributions of frequency, percentage, mean, and standard deviation. and hypothesis testing statistics, paired samples t-test. The results showed that after organizing activities to develop behaviors for the prevention of COVID-19, the sample had a level of knowledge about COVID-19. Increased to a high level of 83.20 percent, with an average score of knowledge about COVID-19. Before and after activities to develop preventive behaviors against COVID-19, there were significantly different at .05 level, the 95% CI confidence interval of the mean difference was between 1.39 - 1.57 points, and there were behavior levels in practice in preventing COVID-19. Increased to a high level, 61.89 percent, with an average score of preventive behavior for COVID-19. Before and after the activities to develop preventive behaviors for COVID-19, they were significantly different at .05 level, with a 95% CI for the mean difference between 1.85 - 1.91 points.